Strategies for the Photoreduction of Tc‐99 Pertechnetate to Low‐Valent Tc by Keggin Polyoxometalates. Issue 22 (11th May 2020) - Radivojevic Jovanovic, Ivana; Gallagher, Colleen M. B.; Salcedo, Ramsey; Lukens, Wayne W.; Burton‐Pye, Benjamin P.; McGregor, Donna; Francesconi, Lynn C.
Abstract : Technetium‐99 (half‐life of 2.1 × 10 5 yrs, βmax = 0.29 MeV) is a hazardous radiological contaminant, which, in its predominant form of pertechnetate (TcO4 – ), is highly mobile in the environment. Most strategies for the removal of pertechnetate from the environment involve uptake and/or absorption of pertechnetate using resins, clays, cationic metal‐organic frameworks and even thorium borate ceramic like materials. Alternative approaches have involved the reduction and subsequent sequestration of lower valent technetium species using iron, sulfides, or iron sulfides. Our lab has explored this strategy using the lacunary alpha‐2 Wells–Dawson polyoxometalate (α2 ‐[P2 W17 O61 ] 10– ) to both reduce and sequester lower valent technetium, and we have reported on the ligand features that stabilize the reduced species. In this work we investigate the potential of "plenary" Keggin POMs (XW12 O40 n – ) (X = P, Si, Al, n = 3, 4, 5, respectively) to both reduce TcO4 – and stabilize the reduced Tc species. Specifically, we report on the mechanism by which the reduction of technetium occurs and find that PW12, SiW12, and AlW12 promote the reduction of TcO4 – to lower valent states. X‐ray absorption spectroscopy was used to confirm a combination of Tc IV {in the form of TcO2 · 2H2 O and Tc2 (µ‐O)2 4+ } and Tc V, which is subsequently complexed into a POM defect as a Tc V =O species. Abstract : We report on the mechanism by which the reduction of technetium occurs and find that PW12, SiW12, and AlW12 promote the reduction of TcO4 – to lower valent states. X‐ray Absorption Spectroscopy (XAS) was used to confirm a combination of Tc IV {in the form of TcO2 · 2H2 O and Tc2 (µ‐O)2 4+ } and Tc V, which is subsequently complexed into a POM defect as a Tc V =O species.